Answer :

Let a be the first term and d be the common difference.

Given: a9 = - 32


a11 + a13 = - 94


To find: common difference = d


Now, Consider a9 = - 32


a + (9 - 1)d = - 32


a + 8d = - 32 ……….(1)


Consider a11 + a13 = - 94


a + (11 - 1)d + a + (13 - 1)d = - 94


2a + 22d = - 94


a + 11d = - 47 ……..(2)


Subtracting equation (1) from equation (2), we get,


3d = - 15


d = - 5


Common difference = d = - 5

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses